Short-Term Forecast of Ukrainian Economy Including Shadow Sector Using Causal Simulation Model - Vasylenko, Yuriy (Ekonomika, 2020)
A new causal simulation model of economic development was created, which comprehensively in detail and fully reflects various types of legal and shadow economic activities and their interrelations.The model is used to forecast the whole (legal and shadow) country’s economy up to 2022.The dynamics of shadow and legal indicators are different.The biggest and most important difference is about exports and imports. Official statistics give a negative balance of the Ukrainian foreign trade of Ukraine in 2019-22. However, total export, determined by the model, considerably exceeds imports, so actually we expect a surplus.This is very important for the National Bank: its policy based on the official (legal) negative balance of Ukraine foreign trade should be one (throw foreign currency reserves into the market or to devalue the hryvnia), but with the actual balance that includes shadow flows and is positive, - contrary one (to buy currency on the market or to revalue the national currency).Our model calculates how the production volumes of all types of goods and services should change to ensure that supply and demand are balanced. These numbers can serve a reference for manufacturers.We suggested that the relevant Ukrainian authorities take an active position in the implementation of the developed forecast for the economic development of Ukraine: measuring actual rates of changes in the production of these types of goods during the year, they provide recommendations to producers to increase or decrease their production.
Keywords: model of legal and shadow economic activities; forecast; active implementation of a forecast